An RNA-Seq Analysis of Grape Plantlets Grown in vitro Reveals Different Responses to Blue, Green, Red LED Light, and White Fluorescent Light - Li, Chun-Xia; Xu, Zhi-Gang; Dong, Rui-Qi; Chang, Sheng-Xin; Wang, Lian-Zhen; Khalil-Ur-Rehman, Muhammad; Tao, Jian-Min (Frontiers in Plant Science, 2017)
Using an RNA sequencing (RNA-seq) approach, we analyzed the differentially expressed genes (DEGs) and physiological behaviors of 'Manicure Finger' grape plantlets grown in vitro under white, blue, green and red light. A total of 670, 1601 and 746 DEGs were identified in plants exposed to blue, green and red light, respectively, compared to the control (white light). By comparing the gene expression patterns with the growth and physiological responses of the grape plantlets, we were able to link the responses of the plants to light of different spectral wavelengths and the expression of particular sets of genes. Exposure to red and green light primarily triggered responses associated with the shade-avoidance syndrome (SAS), such as enhanced elongation of stems, reduced investment in leaf growth and decreased chlorophyll levels accompanied by the expression of genes encoding histone H3, auxin repressed protein, xyloglucan endotransglycosylase/hydrolase, the ELIP protein and microtubule proteins. Furthermore, specific light treatments were associated with the expression of a large number of genes, including those involved in the glucan metabolic pathway and the starch and sucrose metabolic pathways; these genes were up/down-regulated in ways that may explain the increase in the starch, sucrose and total sugar contents in the plants. Moreover, the enhanced root growth and up-regulation of the expression of defense genes accompanied with SAS after exposure to red and green light may be related to the addition of 30 g/L sucrose to the culture medium of plantlets grown in vitro. In contrast, blue light induced the up-regulation of genes related to microtubules, serine carboxypeptidase, chlorophyll synthesis and sugar degradation and the down-regulation of auxin-repressed protein as well as a large number of resistance-related genes that may promote leaf growth, improve chlorophyll synthesis and chloroplast development, increase the ratio of chlorophyll a (chla)/chlorophyll b (chlb), and decrease the ratio of carbohydrates to proteins in plants. Although exposure to red and green light seems to impose “shade stress” on the plantlets, growth under blue light is comparable to growth observed under white or broad-spectrum light.